Directive Illocutionary Acts Used in Mission: Impossible- Fallout Movie - Diah Savitri, Yolanda; Widiastuti, Ni Made Ayu (e-Journal of Linguistics, 2021)
This study aims to find out the types of directive illocutionary acts performed by the characters in the Mission: Impossible-Fallout movie based on the theory of Keith Allan. The subject of this research is the conversations that occur to the characters. This study was conducted by using the descriptive qualitative method. The object of this research is Mission: Impossible - Fallout Movie script. The results of the study show that there are six types of directive illocutionary acts of the Movie. The type of directive that is often used in the movie is a question (39 utterances) which is often used to interrogate sources who have information regarding the IMF mission to find John Lark’s whereabouts and permission (3 words) is a type of directive that is rarely used in this film.